Treatment of Stable Angina Pectoris With Ivabradine in Everyday Practice: A Pan‐Hellenic, Prospective, Noninterventional Study. Issue 12 (19th November 2015) - Zarifis, John; Grammatikou, Violetta; Kallistratos, Manolis; Katsivas, Apostolos; ,
ABSTRACT: Introduction: In coronary artery disease (CAD), medical treatment is the main clinical strategy for controlling ischemia and angina symptoms while restoring a satisfactory level of usual activities and improving quality of life (QOL). This study's purpose was to evaluate in CAD patients the antianginal efficacy of 4‐month treatment with ivabradine plus a β‐blocker and to record patient compliance and the effect of treatment on QOL. Methods: In this noninterventional study, 2403 patients with chronic stable angina were prospectively studied from 245 private cardiology offices. Data were recorded at baseline and at 1 and 4 months after inclusion. Patient quality of life was assessed using the EuroQol 5 dimensions (EQ‐5D) questionnaire. Results: From baseline to study completion, mean heart rate decreased from 81.5 ± 9.7 bpm to 63.9 ± 6.0 bpm (P <‐0.001), mean number of anginal attacks decreased from 2.0 ± 2.0 times/wk to 0.2 ± 0.6 times/wk (P < 0.001) and nitroglycerin consumption decreased from 1.4 ± 2.0 times/wk to 0.1 ± 0.4 times/wk (P < 0.001). The percentage of patients with Canadian Cardiovascular Society angina class I increased from approximately 38% (baseline) to 84% (study completion; P < 0.001). The reduction in anginal attacks, nitroglycerin consumption, and angina score was correlated with reduction in heart rate (P < 0.001). The mean EQ‐5D visual analogue scale index increased by 16.1 points (P < 0.001), and compliance with treatment was high throughout the trial (96%). Conclusions: Ivabradine administration on top of optimal individualized dose of β‐blockers is associated with decreased anginal events and with improvement of QOL in CAD patients.